APLIKASI BUKU TAMU BERBASIS WEBSITE DI PT. PLN (PERSERO) ULP LHOKSUKON . - Zahra, Annisa Afrilia; Suwanda, Rizki (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2023)
A guest book is a tool to find out the number or how many guests have come to a place. Problems faced in the process of recording guest books at PT. PLN (Persero) Lhoksukon ULP is a process that is still manual in its recording or data collection, where the user has to fill in guest data in the guest agenda book which results in a lot of waste of material and the risk of losing data, so that it does not run effectively and efficiently. The aim of developing the system that will be developed is to make it easier for users to register guests and print monthly guest data if needed. This website was developed using the PHP and HTML programming languages, Codeigniter as a framework, and MySQL as data storage. The solution applied in developing this application is to use the UML (Unified Modeling Language) system design method. In this process, use case diagrams are used to explain the activities carried out by users, class diagrams to explain the data structure of the system, activity diagrams to describe user interactions with related objects in the system. The result of developing this system is an application called the Website-Based Guest Book Application at PT. PLN (Persero) ULP Lhoksukon. In this application, users can fill in guest data and print guest data in a computerized manner so that it becomes more effective and efficient.